ANALISIS CAMPUR KODE DALAM LIRIK LAGU GENTLEMAN OLEH BOYBAND SHINEE KARYA JUNJI ISHIWATARI - Dewi, Sifta Sari; Pujiono, Muhammad (IZUMI, 2018)
(Title: The Code Mix Analysis In Lyrics Of Shinee’s Gentleman By Junji Ishiwatari) This study aims to analyze the code mix in the lyrics of SHINee’s Gentleman by Junji Ishiwatari which specifically to describe what kind of code mix is contained in the lyrics and to describe how the factors caused the interference of code in the lyrics. The method used in this research is observation and library research. There are 16 forms of code mix contained in the lyrics, namely: 5 insertion of elements of tangible word, 9 insertion of elements of the phrase and 2 insertion elements of tangible clause. The dominant form of code mix is the insertion of phrasal elements. While there are 3 factors that caused the interference of the code in the lyrics, namely: (1) The casuality (informal situation), (2) The author wants to show the learning and/or position and (3) There is no correctly expression in language that had been used. The dominant factor of them is no correctly expression in language that had been used. The customary factor is not found in the lyrics of SHINee’Gentleman by Junji Ishiwatari although songwriters often use English in writing song lyrics. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor